On the practice of rapid blood pressure reduction with oral medications. A scientific view - A. D. Erlikh; A. V. Rodionov; I. S. Yavelov; D. Yu. Shchekochikhin; V. V. Kashtalap; S. Yu. Martsevich; S. T. Matskeplishvili (Кардиоваскулярная терапия и профилактика, 2025)
Contrary to modern guidelines for the treatment of hypertension, oral and sublingual antihypertensive medications are often used in real-world practice to quickly reduce asymptomatic or low-symptom elevated blood pressure (BP). Doctors and patients explain this by the need to "stop an uncomplicated hypertensive crisis" for preventing cardiovascular events. Clinical trial data indicate that such an approach, both the prescription of short-acting drugs at an outpatient or inpatient levels, and recommendations for self-treatment of hypertension, not only does not benefit the patient, but is also likely to be associated with an increased risk of cardiovascular events. Shifting the focus of hypertension treatment from improving the long-term prognosis to immediate BP reduction may increase short-term variability of BP, which is a possible mechanism for the development of complications when using fast-acting oral antihypertensives. The article substantiates the unacceptability of emergency BP reduction with oral and sublingual antihypertensive drugs. It describes rational actions of a physician in case of detection of asymptomatic or low-symptom BP increase in a patient and presents possible approaches to home BP self-monitoring in accordance with modern clinical guidelines. It also describes the management of true hypertensive crises depending on the characteristics of hypertension-mediated organ damage.